Partner involvement in treatment-related decision making in triadic clinical consultations – A systematic review of qualitative and quantitative studies. Issue 2 (February 2020) - Bracher, Mike; Stewart, Simon; Reidy, Claire; Allen, Chris; Townsend, Kay; Brindle, Lucy
Highlights: Partners often involved in consultations with implications for treatment decisions. Literature lacks direct observation and analysis of communicative processes. Research should explore: partner involvement vs. other companion types in triads. relationships between partner involvement and decision-making processes. Abstract: Objective: Explore how partners are involved in treatment-related decision-making within triadic clinical encounters. Methods: Studies were identified via database searches and reference lists. One author assessed eligibility of studies, which were verified by an additional co-author. Data were extracted by one author and cross-checked for accuracy by a second. Quality of articles was assessed using Qualsyst. Retrieved studies were categorised by one author, and agreed through discussion. Results: From 2442 records, 14 studies were included and categorised as: (1) Descriptions of partner role and behaviour; (2) Role intentions of partners; (3) Relationship between partner and patient behaviour; (4) HCP-Partner interactions. Conclusion: Partners are often involved in triadic clinical consultations that have implications for treatment-related decision making. Most studies offered general descriptions but lacked detailed investigation of communicative processes in triads and how these may operate with partners vs. other companions. Practice implications: Existing studies lack detailed investigation through direct observation of the processes of partner involvement. Research in other areas of clinical communication suggests that future interventions could be informed by attention to the following areas: partner behaviour vs. other companion types in triads; relationships between partner involvement and decision-making processes; partner involvement in triads vs. other groups (e.g. quadratic).